The Martian chronicles [compact disc, unabridged] - Bradbury, Ray. 1920-2012 (Blackstone Audio, 2009)
Leaving behind a world on the brink of destruction, man came to the Red Planet and found the Martians waiting, dreamlike. Seeking the promise of a new beginning, man brought with him his oldest fears and his deepest desires. Man conquered Mars-- and in that instant, Mars conquered him. The strange new world, with its ancient, dying race and vast red-gold deserts, cast a spell on him, settled into his dreams, and changed him forever.